PENGARUH PENAMBAHAN UREA DAN MELAMIN PADA PEREKAT UREA FORMALDEHIDA TERHADAP EMISI FORMALDEHIDA DAN SIFAT FISIS-MEKANIS PAPAN PARTIKEL - Paribotro Sutigno; Adi Santoso (Jurnal Penelitian Hasil Hutan, 1996)
The formaldehyde  emtsston of particleboard  bonded  with  urea formaldehyde  (UF) can affect health, especially if it is used in a room with limited ventilation.  To reduce formaldehyde emission,  the glue can be mixed with catching agent.  In this report, the effect of using urea and melamine as catching agents on formaldehyde  emission,   and on the physical  and mechanical properties  of UF bonded particleboard is described.The effect of percentage  of catching agent on formaldehyde  emission is highly significant. The higher  the percentage  of catching agent,  the lower formaldehyde  emission of particleboard.  On ureamelamine  (U/M) ratio of  4,  the formaldehyde  emission of particleboard  can meet American  and Japanese  Standard on the percentage  of 5,  10  and 15%,  while on  U/M ratio of 7 and 10,  the formaldehyde  emission can conform the standards on the percentage  of 10  and 15%.   The effect  of addition of  urea and melamine  was significant and  even highly significant on the physical and mechanical properties,  but not on the shear strength.  The effect of U/M ratio was either not significant.Key words :  particleboard,  urea-melamine,  formaldehyde emission,  physical and  mechanical properties.